Van der Waals solid solution crystals for highly efficient in-air photon upconversion under subsolar irradiance. Issue 12 (9th November 2021) - Enomoto, Riku; Hoshi, Megumi; Oyama, Hironaga; Agata, Hideki; Kurokawa, Shinichi; Kuma, Hitoshi; Uekusa, Hidehiro; Murakami, Yoichi
Abstract : The concept of van der Waals solid solutions has been demonstrated to yield photon upconversion (UC) organic crystals with extraordinary performance, opening a domain of versatile dispersion-force-based systems in the quest for superior UC solids. Abstract : Triplet-sensitized photon upconversion (UC) has been proposed for broad applications. However, the quest for superior solid materials has been challenged by the poor exciton transport often caused by low crystallinity, a small crystal domain, and aggregation of triplet sensitizers. Here, we demonstrate substantial advantages of the van der Waals solid solution concept to yield molecular crystals with extraordinary performance. A 0.001%-order porphyrin sensitizer is dissolved during recrystallization into the molecular crystals of a blue-fluorescent hydrocarbon annihilator, 9-(2-naphthyl)-10-[4-(1-naphthyl)phenyl]anthracene (ANNP), which contains bulky side groups. This attempt yields millimeter-sized, uniformly colored, transparent solid solution crystals, which resolves the long-standing problem of sensitizer aggregation. After annealing, the crystals exhibit unprecedented UC performance (UC quantum yield reaching 16% out of a maximum of 50% by definition; excitation intensity threshold of 0.175 sun; and high photostability of over 150 000 s) in air, which proves that this concept is highly effective in the quest for superior UC solid materials.